Adenosine stimulates angiogenesis by up-regulating production of thrombospondin-1 by macrophages. Issue 1 (11th November 2014) - Ernens, Isabelle; Bousquenaud, Me´lanie; Lenoir, Be´ne´dicte; Devaux, Yvan; Wagner, Daniel R
Abstract : Adenosine modulation of thrombospondin-1 expression by macrophages stimulates angiogenesis. Abstract: Increase of blood capillary density at the interface between normal and ischemic tissue after acute MI reduces infarct size and improves cardiac function. Cardiac injury triggers the production of the matricellular component TSP-1, but its role in angiogenesis is not clear, as both anti- and proangiogenic properties have been reported. It is unknown whether TSP-1 is modulated by other factors released during cardiac injury. Among these, Ado is a well-known promoter of angiogenesis. This study determined whether Ado modulates TSP-1 expression and the implication on angiogenesis. Ado dose dependently increased the production of TSP-1 by human macrophages. With the use of agonists and antagonists of AdoRs, coupled to RNA interference, we observed that this effect is mediated via A2A R and A2B R. The Ado effect was reproduced by cholera toxin (Gs protein activator) and forskolin (adenylate cyclase activator) and blocked by the PKA inhibitor H89. Conditioned medium from Ado-treated macrophages stimulated microvessel outgrowth from aortic ring explants by 400%, and induced vessel formation in matrigel plugs. Microvessel outgrowth and vessel formation were blocked completely by addition of anti-TSP-1 antibodies to conditioned medium. Chronic administration of Ado to rats after MI maintained long-term expression of TSP-1 in the infarct border zone, and this was associated with enhanced border-zone vascularization. Ado up-regulates TSP-1 production by macrophages, resulting in stimulation of angiogenesis. The mechanism involves A2A R and A2B R and is mediated through the cAMP/PKA pathway. This information may be important when designing Ado-based therapies of angiogenesis.